Endoscopic Submucosal Tunnel Dissection as a Novel Therapeutic Technique in Patients With Barrett's Esophagus - Faisal Inayat MBBS; Simcha Weissman DO; Adnan Malik MD; Badria Munir MBBS; Shahzad Iqbal MD (SAGE Publishing, 2020)
With the ameliorated resectability prowess of endoscopic techniques, a myriad of diseases previously treated by major ablative surgeries are now endoscopically curable. Endoscopic submucosal tunnel dissection (ESTD) is a relatively new technique that has diversified endoscopic application. Although ESTD has frequently been used for the resection of esophageal neoplastic lesions, the clinical evidence pertaining to its efficacy in the treatment of circumferential Barrett's esophagus remains sparse. In this study, we evaluated ESTD as a potential therapeutic technique in patients with Barrett's esophagus-related high-grade dysplasia. The tunneling strategy helped achieve complete en bloc resection at an increased dissection speed, without any procedural complications. This article illustrates that ESTD can be a feasible, safe, and effective treatment for dysplastic Barrett's esophagus. Future research should aim to stratify the potential risks and complications associated with this optimization of endoscopic submucosal dissection in patients with superficial esophageal lesions.